Effect of compost formulation and postharvest management on quality parameters of button mushroom - Mohammad Ebrahim Ranjbar; Zahra Ghahremani (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The main objective of the present study was to evaluate the effects of compost formulation made from agricultural by-products and thermal treatment of fresh mushrooms on the postharvest quality parameters. Methods Quail manure was evaluated as an alternative ingredient to the broadly used chicken manure for compost preparation. In addition, the treatment of fresh mushrooms by hot water to extend shelf-life was tested. Quality parameters including color (browning due to microbial activity), cap opening and the weight loss (senescence) were evaluated. Results The nature of the manure employed as base material in the substrate can affect the postharvest browning ratio of mushroom. However, no significant differences in Îb value, weight loss or cap opening were noticed between two different substrates during storage of harvested mushrooms. The cap opening ratio was further retarded while applying thermal treatment to the mushrooms at 55 °C. Conclusions The use of chicken manure as base material to prepare mushroom substrate reduces mushroom browning during storage compared to quail manure, although mushrooms from quail compost are whiter at picking. Postharvest treatment at 45 °C for 4 min was the best to minimize the weight loss.